Kepemimpinan Transformasional Berbasis Nilai Spiritual Dalam Peningkatan Religiusitas Pendidik Dan Peserta Didik - Zaini, Fawaid (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
Leadership in education plays a crucial role in determining the direction, quality, and effectiveness of the learning process. This study examines transformational leadership based on spiritual values as a strategy to enhance the religiosity of educators and students at Madrasah Aliyah Negeri (MAN) Sumenep. A qualitative case study approach was employed, with data collected through observations, interviews, and documentation. The findings reveal that transformational leadership at MAN Sumenep is implemented through four key dimensions: (1) Idealized Influence, where the head of the madrasah serves as a role model in religious practices; (2) Inspirational Motivation, which fosters religious enthusiasm through sermons and Islamic activities; (3) Intellectual Stimulation, involving regular evaluations to strengthen religious culture; and (4) Individualized Consideration, which focuses on the spiritual and moral development of students. This leadership approach is carried out through various programs, including congregational prayers, Quran recitation sessions, collective supplications before and after lessons, and the commemoration of Islamic holidays (PHBI). Additionally, a spiritual attendance system is implemented to monitor students' discipline in practicing religious obligations. The study concludes that transformational leadership based on spiritual values effectively fosters an educational environment that not only enhances academic quality but also strengthens students' religious character. This leadership model can serve as a reference for other educational institutions seeking to integrate spiritual values into their educational systems.